Genetic Evidence for a Potential Environmental Pathway to Spillover Infection of Rat-Borne Leptospirosis. (17th June 2021) - Casanovas-Massana, Arnau; de Oliveira, Daiana; Schneider, Andrew G; Begon, Mike; Childs, James E; Costa, Federico; Reis, Mitermayer G; Ko, Albert I; Wunder, Elsio A
Abstract: In this study, we genotyped samples from environmental reservoirs (surface water and soil), colonized rat specimens, and cases of human severe leptospirosis from an endemic urban slum in Brazil, to determine the molecular epidemiology of pathogenic Leptospira and identify pathways of leptospirosis infection. We identified a well-established population of Leptospira interrogans serovar Copenhageni common to human leptospirosis cases, and animal and environmental reservoirs. This finding provides genetic evidence for a potential environmental spillover pathway for rat-borne leptospirosis through the environment in this urban community and highlights the importance of environmental and social interventions to reduce spillover infections.